Pemberdayaan SDM Berbasis Islam dalam Meningkatkan Keunggulan Bersaing Organisasi: Suatu Pendekatan Manajemen Strategik - Syahidin, Mohamad Rizal (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim to be achieved in this research is to find out what is related to empowering human resources to increase competitive advantage in an organization. The method used in this research is qualitative by conducting various interviews with several informants. The results of this research show that the human resource management cycle with the PDAC cycle contains four parts, including planning, implementation, evaluation and follow-up. According to past views, HR empowerment aimed at competitive advantage is something valid where in the modern era humans are required to be able to think and develop in a better direction. Keywords: Competitive Advantage, Empowerment, HR.